Sodium ion battery

By adding sodium salted additives and negative active materials to sodium ions battery, and optimizing the quality and particle size of sodium supplement additives, the problem of lowering the low and low circulation performance of existing sodium ion batteries, and realizing the battery performance of the battery performance promote.

CN119340473AActive Publication Date: 2025-01-21SHENZHEN CAPCHEM TECH CO LTD

Patent Information

Application Number
CN202310881878.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-01-21
Estimated Expiration
2043-07-18

AI Technical Summary

Technical Problem

The existing sodium ion batteries with sodium-enriched transition metal oxides added with sodium-enriched sodium-enriched transition metal oxides have low first-term efficiency and low cycle performance.

Method used

By adding sodium salt-type additives and negative active materials to sodium-ion batteries, and optimizing the mass content and particle size of the sodium-supplementing additives to meet a specific mass ratio relationship, battery performance can be improved with a synergistic effect.

Benefits of technology

It effectively improves the conductivity of the electrolyte and the diffusion and transmission rate of ions in the negative electrode material, reduces the internal resistance of the battery, and improves the first efficiency and cycle performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004344991410000101
    Figure BDA0004344991410000101
  • Figure BDA0004344991410000111
    Figure BDA0004344991410000111
  • Figure BDA0004344991410000131
    Figure BDA0004344991410000131
Patent Text Reader

Abstract

In order to solve the technical problems of low first efficiency and low cycle performance of the conventional sodium ion battery added with a sodium-supplementing additive of a sodium-rich transition metal oxide, the invention provides a sodium ion battery which comprises a non-aqueous electrolyte, a positive electrode and a negative electrode, the non-aqueous electrolyte comprises an additive, the additive comprises a sodium salt type additive, the positive electrode comprises a positive electrode active material layer, and the negative electrode comprises a negative electrode active material layer. The positive active material layer comprises a sodium supplement additive and a positive active material, and the sodium supplement additive is a sodium-rich transition metal oxide; the sodium ion battery meets the following relational expressions: 0.3 < = a / (b + c) < = 1.5, 5 < = a < = 10, 1 < = b < = 10, and 2 < = c < = 12; according to the sodium-ion battery, the internal resistance of the battery is reduced, and the first efficiency and cycle performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a sodium ion battery. Background Art

[0002] Sodium-ion batteries are similar to lithium-ion batteries in principle and structure. Compared with lithium batteries, sodium-ion batteries have wide resources, low costs, small fluctuations, and wide temperature range and high safety performance, which give them alternative potential. With the continuous advancement of sodium-ion battery technology, sodium-ion batteries will occupy an important position in my country's energy system, especially in the field of energy storage, which has a broad growth space. Therefore, the development of high-performance, low-cost sodium-ion batteries is the decisive factor in determining whether they can be industrialized. Due to its stable structure, high conductivity, high sodium storage, and high capacity, hard carbon has become one of the most excellent and most likely negative electrode materials in sodium-ion batteries. However, due to the many defects and large specific surface area of ​​hard carbon, the formation of its SEI film (solid electrolyte membrane) and the electrode interface side reactions are accompanied by more serious irreversible loss of sodium ions, which directly affects the energy density and cycle life of sodium-ion batteries, especially the impact on sodium-ion full batteries is greater. In response to the above problems, researchers have compensated for the irreversible sodium ion loss through various sodium supplementation technologies to improve the initial efficiency of sodium-ion batteries. For example, the existing Chinese patent CN111293290A discloses a sodium-rich transition metal oxide composite sodium-supplementing positive electrode active material, wherein the sodium-supplementing additive is a sodium-rich transition metal oxide with a chemical formula of Na x MO y ; Wherein, M is one or more of Ni, Co, Fe, Mn, Ru, Ir, Sn, Cr, Cu, Nb, and Mo. This material uses two or more sodium supplement materials mixed as a positive electrode additive, which can effectively compensate for the active sodium loss of the sodium ion battery. However, the sodium-rich metal oxide used as a sodium supplement additive has the characteristics of poor conductivity, high impedance, high activity, and easy decomposition and gas production. The prepared battery has low initial efficiency and poor cycle performance. Therefore, it is of great significance to develop a sodium ion battery that can improve the sodium supplement additive by adding sodium-rich transition metal oxides. Summary of the invention

[0003] In order to solve the technical problems that the existing sodium ion batteries to which sodium-rich transition metal oxide sodium supplement additives are added have low initial efficiency and low cycle performance, the present application provides a sodium ion battery.

[0004] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0005] On the one hand, the present application provides a sodium ion battery, comprising a non-aqueous electrolyte, a positive electrode and a negative electrode, wherein the non-aqueous electrolyte comprises an additive, wherein the additive comprises a sodium salt-type additive, the positive electrode comprises a positive electrode active material layer, wherein the positive electrode active material layer comprises a sodium supplement additive and a positive electrode active material, wherein the sodium supplement additive is a sodium-rich transition metal oxide; the negative electrode comprises a negative electrode active material,

[0006] The sodium ion battery satisfies the following relationship:

[0007] 0.3≤a / (b+c)≤1.5, and 5≤a≤10, 1≤b≤10, 2≤c≤12;

[0008] Wherein, the total mass of the sodium supplement additive and the positive electrode active material is 100%, a is the mass content of the sodium supplement additive, unit %;

[0009] b is the mass content of the sodium salt type additive in the non-aqueous electrolyte, in %;

[0010] c is the particle size of the negative electrode active material, in μm.

[0011] Preferably, the sodium ion battery satisfies the following relationship: 0.5≤a / (b+c)≤1.2.

[0012] Preferably, the total mass of the sodium supplement additive and the positive electrode active material is 100%, and the mass content a of the sodium supplement additive is in the range of 5.5-9%.

[0013] Preferably, the sodium salt additive includes one or more of sodium bis(fluorosulfonyl)imide, sodium difluorooxalatoborate, and sodium difluorophosphate;

[0014] The mass content b of the sodium salt additive in the non-aqueous electrolyte is in the range of 2% to 6%.

[0015] Preferably, the particle size c of the negative electrode active material is in the range of 3 μm to 9 μm.

[0016] Preferably, the additive further comprises 1,3-propane sultone, and the mass content of the 1,3-propane sultone in the non-aqueous electrolyte is 0.5% to 2%.

[0017] Preferably, the mass content of the 1,3-propane sultone in the non-aqueous electrolyte is 1% to 2%.

[0018] Preferably, the sodium-rich transition metal oxide comprises a compound represented by Formula 1,

[0019] Na x M y O z Formula 1,

[0020] Among them, 0.2<x / y<9, 0<y<6, 2≤z≤9, and M is selected from one or more of Nb, V, Ta, Mn, Fe, Cr, Co, Ni, Cu, Zn, Mg, Ti, Si, Sn, Ce, and Zr.

[0021] Preferably, the sodium-rich transition metal oxide comprises Na 5 NbO 5 、Na 3 NbO 4 、Na 4 Nb 2 O 7 、Na 5 VO 5 、Na 3 VO 4 、Na 3 TaO 4 One or more of .

[0022] Preferably, the non-aqueous electrolyte further comprises an electrolyte salt, an auxiliary additive and a non-aqueous organic solvent.

[0023] The electrolyte salt includes at least one of sodium hexafluorophosphate, sodium trifluoromethylsulfonyl imide, sodium trifluoromethylsulfonate, sodium tetrafluoroborate, sodium perchlorate, sodium hexafluoroarsenate, sodium trifluoroacetate, sodium tetraphenylborate and sodium bis(trifluoromethylsulfonyl)imide;

[0024] The mass content of the electrolyte salt is 8% to 14% based on the mass of the electrolyte solution being 100%;

[0025] The auxiliary additive includes at least one of 1,4-butane sultone, acrylic acid lactone, vinyl sulfate and fluoroethylene carbonate;

[0026] Taking the mass of the electrolyte as 100%, the mass content of the auxiliary additive is 2.5% to 10%;

[0027] The non-aqueous organic solvent includes at least one of carbonates with 3 to 5 carbon atoms, carboxylates with 2 to 6 carbon atoms, and ethers with 4 to 10 carbon atoms;

[0028] The positive electrode active material includes at least one of layered transition metal oxides, Prussian compounds, phosphate compounds, and sulfate compounds;

[0029] The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes one or more of a carbon-based material, a silicon-based material, and a tin-based material.

[0030] Beneficial effects:

[0031] In the sodium ion battery provided by the present application, the total mass of the sodium supplement additive and the positive electrode active material is 100%, a is the mass content of the sodium supplement additive, and it has a synergistic effect with the sodium salt type additive and the negative electrode active material, and there is a certain relationship between the mass content a of the sodium supplement additive and the mass content b of the sodium salt type additive added to the electrolyte and the particle size c of the negative electrode active material. When a, b, and c satisfy the relationship 0.3≤a / (b+c)≤1.5, it can effectively improve the conductivity of the electrolyte and the diffusion and transmission rate of ions in the negative electrode material while ensuring the optimal conductivity of the positive electrode, thereby effectively reducing the overall internal resistance of the battery and improving the first efficiency and cycle performance of the battery; in addition, the addition of the sodium salt type additive in the electrolyte will also participate in the formation of the positive and negative electrode interface film, effectively protecting the stability of the negative electrode in the test, thereby further improving the cycle performance. DETAILED DESCRIPTION

[0032] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] On one hand, the present application provides a sodium ion battery, comprising a non-aqueous electrolyte, a positive electrode and a negative electrode, wherein the non-aqueous electrolyte comprises an additive, wherein the additive comprises a sodium salt-type additive, the positive electrode comprises a positive electrode active material layer, wherein the positive electrode active material layer comprises a sodium supplement additive and a positive electrode active material, wherein the sodium supplement additive is a sodium-rich transition metal oxide; the negative electrode comprises a negative electrode active material,

[0034] The sodium ion battery satisfies the following relationship:

[0035] 0.3≤a / (b+c)≤1.5, and 5≤a≤10, 1≤b≤10, 2≤c≤12;

[0036] Wherein, the total mass of the sodium supplement additive and the positive electrode active material is 100%, a is the mass content of the sodium supplement additive, unit %;

[0037] b is the mass content of the sodium salt type additive in the non-aqueous electrolyte, in %;

[0038] c is the particle size of the negative electrode active material, in μm.

[0039] A sodium-rich transition metal oxide is added to a sodium ion battery as a sodium supplement additive. The sodium supplement additive has the characteristics of poor conductivity, high impedance, high activity, and easy decomposition and gas production. The prepared battery has low first efficiency and cycle performance. In response to this problem, the inventors have found through extensive research that the total mass of the sodium supplement additive and the positive electrode active material is 100%, a is the mass content of the sodium supplement additive, and it has a synergistic effect with the sodium salt type additive and the negative electrode active material. There is a certain relationship between the mass content a of the sodium supplement additive and the mass content b of the sodium salt type additive added to the electrolyte and the particle size c of the negative electrode active material. When a, b, and c satisfy the relationship 0.3≤a / (b+c)≤1.5, it can effectively improve the conductivity of the electrolyte and the diffusion and transmission rate of ions in the negative electrode material while ensuring the optimal conductivity of the positive electrode, thereby effectively reducing the overall internal resistance of the battery and improving the first efficiency and cycle performance of the battery. In addition, the addition of the sodium salt type additive in the electrolyte will also participate in the formation of the positive and negative electrode interface film, effectively protecting the stability of the negative electrode in the test, thereby further improving the cycle performance.

[0040] In some preferred embodiments, the sodium ion battery satisfies the following relationship: 0.5≤a / (b+c)≤1.2.

[0041] Sodium-ion batteries satisfy the relationship 0.5≤a / (b+c)≤1.2. The conductivity of the positive electrode is relatively high, and the conductivity of the electrolyte is greatly improved, which increases the diffusion and transmission rate of sodium ions in the negative electrode active material, thereby effectively reducing the overall internal resistance of the battery and improving the battery's initial efficiency and cycle performance. In addition, the addition of sodium salt additives to the electrolyte will also participate in the negative electrode film formation, and can form a more stable interface film at the electrode interface, preventing the residual by-products of the sodium supplement additive from damaging the positive and negative electrodes, effectively protecting the stability of the negative electrode in the test, and further improving the cycle performance.

[0042] Specifically, the value of the sodium ion battery relationship a / (b+c) can be 0.3, 0.5, 0.6, 0.8, 1.0, 1.2, 1.4, 1.5, etc., as long as the relationship a / (b+c) value is between 0.3 and 1.5. Specifically, the mass content b of the sodium salt type additive in the electrolyte in the non-aqueous electrolyte is in the range of 1% to 10%, which has the effect of improving the overall conductivity of the electrolyte, and can also participate in the film formation at the positive and negative electrode interfaces, protect the positive and negative electrodes, and effectively solve the problem of poor conductivity of the sodium supplement additive and the damage of the positive and negative electrodes by the residual by-products, improve the battery performance, and improve the battery cycle performance. If the mass content b of the sodium salt type additive in the electrolyte in the non-aqueous electrolyte is less than 1%, the effect of improving the conductivity of the electrolyte is not obvious, and it cannot effectively participate in the formation of the positive and negative electrode interface film. If b is greater than 10%, the mass content of the sodium salt type additive in the electrolyte is too high, the thickness of the interface film participating in the formation of the electrode interface is thick, the transmission rate of sodium ions is reduced, and the battery impedance increases. Specifically, the mass content b of the sodium salt additive in the electrolyte can be 1, 1.5, 2, 3, 4, 5, 6, 7, 8, 9, 10%, etc., as long as the range of b is between 1% and 10%.

[0043] In some preferred embodiments, the mass content b of the sodium salt additive in the non-aqueous electrolyte is in the range of 2% to 6%.

[0044] The mass content of the sodium salt additive added to the electrolyte is within the above-mentioned preferred range, which can improve the overall conductivity of the electrolyte while forming an interface film with moderate thickness and stable structure at the interface of the positive and negative electrodes, thereby effectively solving the problem of poor conductivity of the sodium supplement additive and damage to the positive and negative electrodes by residual by-products, thereby better improving battery performance and improving battery cycle performance.

[0045] In some embodiments, the sodium salt additive includes sodium bis(fluorosulfonyl)imide (NaFSI), sodium difluorooxalatoborate (NaODFB), sodium difluorophosphate (NaPO 2 F 2 )

[0046] In some embodiments, the total mass of the sodium supplement additive and the positive electrode active material is 100%, and the mass content a of the sodium supplement additive is in the range of 5% to 10%.

[0047] Since the sodium supplement additive itself has poor conductivity and there will be residual byproducts after the reaction, when the mass content a of the sodium supplement additive is greater than 10%, the overall performance of the positive electrode material deteriorates; when the mass content a of the sodium supplement additive is less than 5%, it does not have the effect of sodium supplementation. In sodium ion batteries, the total mass of the sodium supplement additive and the positive electrode active material is 100%, and the mass content a of the sodium supplement additive is between 5% and 10%. The sodium supplement additive can play a good role in sodium supplementation while also improving the conductivity of the positive electrode, and reducing the residual byproducts after the sodium supplement additive reaction, thereby improving the first effect and cycle performance of the battery. Specifically, a can be 5%, 5.5%, 6%, 6.4%, 7.0%, 7.3%, 7.6%, 8.0%, 9%, 10%, etc., as long as the value of a is within the range of 5% to 10%.

[0048] In some preferred embodiments, the total mass of the sodium supplement additive and the positive electrode active material is 100%, and the mass content a of the sodium supplement additive is in the range of 5.5-9%.

[0049] In the above preferred range, the sodium supplement additive in the sodium ion battery can not only play a good role in sodium supplementation, but also improve the conductivity of the positive electrode sheet and improve the initial efficiency and cycle performance of the battery.

[0050] In some embodiments, the sodium-rich transition metal oxide comprises a compound represented by Formula 1,

[0051] Na x M y O z Formula 1,

[0052] Among them, 0.2<x / y<9, 0<y<6, 2≤z≤9, and M is selected from one or more of Nb, V, Ta, Mn, Fe, Cr, Co, Ni, Cu, Zn, Mg, Ti, Si, Sn, Ce, and Zr.

[0053] In some preferred embodiments, the sodium-rich transition metal oxide comprises Na 5 NbO 5 、Na 3 NbO 4 、Na 4 Nb 2 O 7 、Na 5 VO 5 、Na 3 VO 4 、Na 3 TaO 4 It is to be understood that the present application does not limit the types of the above-mentioned sodium-rich transition metal oxides.

[0054] In some embodiments, the particle size c of the negative electrode active material is in the range of 2 μm to 12 μm.

[0055] The particle size of the negative electrode active material of 2 to 12 μm can ensure a faster ion transfer rate within and between the particles of the negative electrode active material, thereby further improving the disadvantage of deteriorating the battery rate performance due to sodium supplementation additives and improving the battery cycle performance. If the particle size c of the negative electrode active material is greater than 12 μm, the internal resistance of the battery increases and the cycle performance is poor; if the particle size c of the negative electrode active material is less than 2 μm, the particle size is too small to reduce the first efficiency of the battery. Specifically, the particle size c of the negative electrode active material can be 3 μm, 4 μm, 5 μm, 5.5 μm, 6 μm, 7.5 μm, 8 μm, 9 μm, 10 μm, 12 μm, etc., as long as c is in the range of 3 μm-12 μm.

[0056] In some preferred embodiments, the particle size c of the negative electrode active material is in the range of 3 μm to 9 μm.

[0057] When the particle size c of the negative electrode active material is within the above preferred range, the transmission efficiency of sodium ions can be better improved, and the cycle performance of the battery can be better improved.

[0058] In some embodiments, the additive further comprises 1,3-propane sultone, and the mass content of the 1,3-propane sultone in the non-aqueous electrolyte is 0.5% to 2%.

[0059] Specifically, 1,3-propane sultone (PS) with a mass content of 0.5% to 2% in the electrolyte can effectively inhibit the occurrence of side reactions on the surface of the electrode and the dissolution and precipitation of metal ions on the surface of the positive electrode, stabilize the crystal structure of the positive electrode, effectively reduce the internal resistance and gas production of the battery, and improve the cycle performance. Specifically, if the PS content in the electrolyte is lower than 0.5%, it cannot effectively inhibit the dissolution and precipitation of metal ions at the positive electrode interface. If the PS content in the electrolyte is higher than 2%, the thickness of the electrode interface film formed in the electrolyte increases, and the battery impedance increases. Specifically, the mass content of 1,3-propane sultone in the electrolyte can be 0.5%, 0.8%, 1.0%, 1.2%, 1.4%, 1.5%, 1.7%, 1.9%, 2.0%, etc., as long as it is between 0.5 and 2%.

[0060] In some preferred embodiments, the mass content of the 1,3-propane sultone in the non-aqueous electrolyte is 1% to 2%.

[0061] The mass content of 1,3-propane sultone is within this preferred range, which can effectively inhibit the dissolution and precipitation of metal ions at the positive electrode interface, and also participate in the formation of a structurally stable interface film, thereby reducing the internal resistance of the battery and the gas production.

[0062] In some embodiments, the non-aqueous electrolyte further comprises an electrolyte salt, wherein the electrolyte salt comprises at least one of sodium hexafluorophosphate, sodium trifluoromethylsulfonyl imide, sodium trifluoromethylsulfonate, sodium tetrafluoroborate, sodium perchlorate, sodium hexafluoroarsenate, sodium trifluoroacetate, sodium tetraphenylborate and sodium bis(trifluoromethylsulfonyl)imide;

[0063] Based on the mass of the electrolyte being 100%, the mass content of the electrolyte salt is 8% to 14%.

[0064] Electrolyte salts are added to the electrolyte, which have high solubility in non-aqueous organic solvents and are easy to dissociate, to ensure that the electrolyte has high ionic conductivity and promote the redox reaction of the battery.

[0065] In some embodiments, the non-aqueous electrolyte further includes an auxiliary additive, and the auxiliary additive includes at least one of 1,4-butane sultone, propylene glycol (RPS), dithiothreitol (DTD) and fluoroethylene carbonate. The mass content of the auxiliary additive is 2.5% to 10% based on the mass of the electrolyte as 100%.

[0066] In some embodiments, the non-aqueous electrolyte further includes a non-aqueous organic solvent, and the non-aqueous organic solvent includes at least one of carbonates with 3 to 5 carbon atoms, carboxylates with 2 to 6 carbon atoms, and ethers with 4 to 10 carbon atoms.

[0067] Preferably, the carbonate solvent having 3 to 5 carbon atoms includes cyclic carbonates or chain carbonates having 3 to 5 carbon atoms, wherein the cyclic carbonates include but are not limited to at least one of ethylene carbonate (EC), vinylene carbonate (VC), vinylethylene carbonate (VEC), propylene carbonate (PC), γ-butyrolactone (GBL), and butylene carbonate (BC); the chain carbonates may specifically be but are not limited to dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dipropyl carbonate (DPC).

[0068] Preferably, the carboxylic acid ester with 2 to 6 carbon atoms includes but is not limited to at least one of methyl acetate (MA), ethyl acetate (EA), propyl acetate (EP), butyl acetate, and propyl propionate (PP). As a preferred solution, the secondary battery non-aqueous electrolyte also includes vinylene carbonate (VC), vinyl ethylene carbonate (VEC), and fluoroethylene carbonate (FEC).

[0069] Preferably, the ether solvent having 4 to 10 carbon atoms includes cyclic ethers or chain ethers having 4 to 10 carbon atoms, and the cyclic ethers include but are not limited to 1,3-dioxolane (DOL), 1,4-dioxolane (DX), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH 3-THF), 2-trifluoromethyltetrahydrofuran (2-CF 3 -THF); the chain ether includes but is not limited to at least one of dimethoxymethane (DMM), 1,2-dimethoxyethane (DME), and diethylene glycol dimethyl ether (TEGDME).

[0070] In some embodiments, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material is selected from at least one of a layered transition metal oxide, a Prussian compound, a phosphate compound, and a sulfate compound;

[0071] The negative electrode includes a negative electrode active material, and the negative electrode active material includes one or more of a carbon-based material, a silicon-based material, and a tin-based material. The carbon-based material includes at least one of hard carbon, soft carbon, carbon nanotubes, graphite, graphene, expanded graphite, or mesophase carbon microspheres.

[0072] In some embodiments, the chemical formula of the layered transition metal oxide compound is Na n L m O r , 0<n≤1, 0<m≤1, 1<r≤2, L can be selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V.

[0073] In a preferred embodiment, the chemical formula of the layered transition metal oxide is Na p Ni m Mn n M (1-m-n) O q , where 0<p≤1, 0≤m<1, 0<m+n<1, 1<q≤2.

[0074] In a more preferred embodiment, the positive electrode active material is Na p' Ni m' Mn n' Fe (1-m'-n') O 2 , wherein 0<p'≤1, 0≤m'<1, 0<m'+n'<1, 1<q'≤2. Further, preferably NaNi 0.3 Mn 0.3 Fe 0.4 O 2 、NaNi 0.4 Mn 0.4 Fe 0.2 O 2 、NaNi 0.5 Mn 0.35 Fe 0.15 O 2 .

[0075] In a more preferred embodiment, the chemical formula of the layered transition metal oxide is NaNi m Co n Mn p O 2 At least one of (m+n+p=1, 0≤m≤1, 0≤n≤1, 0≤p≤1).

[0076] In some embodiments, the molecular formula of the Prussian compound is Na x' M[M′(CN) 6 ] y' ·z'H 2 O, M is a transition metal, M' is a transition metal, 0 <x'≤2,0<y'≤1,0<z'≤20。

[0077] In a more preferred embodiment, the Prussian compound is Na x' Mn[Fe(CN) 6 ] y' ·z'H 2 O or Na x' Fe[Fe(CN) 6 ] y '·z'H 2 O, 0<x'≤2, 0<y'≤1, 0<z'≤20.

[0078] In some embodiments, the chemical formula of the phosphate compound is Na 3 (RO 1-x'' PO 4 ) 2 F 1+2x'' Or Na 2 R′PO 4 F, wherein 0≤x''≤1, R is selected from at least one of Al, V, Ge, Fe, and Ga, and R' is selected from at least one of Fe and Mn.

[0079] In a more preferred embodiment, the chemical formula of the phosphate compound is Na 3 (VPO 4 ) 2 F 3 、Na 3 (VOPO 4 ) 2 F. Na 2 FePO 4 F. Na 2 MnPO 4 F.

[0080] In some embodiments, the chemical formula of the sulfate compound is Na 2 A(SO4 ) 2 ·2H 2 O, A is selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb and V.

[0081] The present invention is further described below by way of examples.

[0082] Example 1

[0083] This embodiment is used to illustrate the sodium ion battery disclosed in this application.

[0084] (1) Preparation of positive electrode: The positive electrode active material NaNi was prepared in a mass ratio of 88.825:6.175:2:3. 0.3 Fe 0.3 Mn 0.4 O 2 , sodium supplement Na 5 NbO 5 , conductive carbon black Super-P and binder polyvinylidene fluoride (PVDF) are mixed, and then dispersed in an appropriate amount of N-methyl-2-pyrrolidone (NMP) to obtain a positive electrode slurry; the obtained slurry is evenly coated on both sides of the aluminum foil, dried, rolled and vacuum dried, and welded with an ultrasonic welder to obtain a positive electrode sheet. Wherein, the total mass of the positive electrode active material and the sodium supplement additive is 100%, the mass content of the sodium supplement additive is a, and a is 6.5%.

[0085] (2) Preparation of negative electrode: According to the mass ratio of 94:1:2.5:2.5, the negative electrode active material hard carbon, conductive carbon black Super-P, binder styrene butadiene rubber (SBR) and carboxymethyl cellulose (CMC) are mixed, and then dispersed in an appropriate amount of deionized water to obtain a negative electrode slurry; the slurry is coated on both sides of the copper foil, and after drying, rolling and vacuum drying, a nickel lead wire is welded with an ultrasonic welder to obtain a negative electrode sheet. The particle size of the negative electrode active material hard carbon is c, and the specific value of c is shown in Table 1.

[0086] (3) Preparation of electrolyte: Ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate were mixed at a mass ratio of EC:PC:EMC=10:15:75, and then sodium hexafluorophosphate with a mass content of 12% was added, sodium salt type additive sodium difluorooxalatoborate with a mass content of b was added, 1,3-propane sultone (PS) was added, and finally auxiliary additives were added to form an electrolyte. The specific types and mass contents of the auxiliary additives, the specific value of b, and the mass content of 1,3-propane sultone are shown in Table 1.

[0087] (4) Preparation of sodium ion battery: A separator is placed between the positive electrode sheet and the negative electrode sheet prepared above, and then a sandwich structure consisting of the positive electrode sheet, the negative electrode sheet and the separator is wound, and then the wound body is flattened and placed in an aluminum foil packaging bag to assemble a battery.

[0088] Examples 2-31 and Comparative Examples 1-11

[0089] The difference between Example 2-31 and Comparative Example 1-11 and Example 1 is that the values ​​of a, c, and b are different, the types and mass contents of the auxiliary additives, and the mass content of 1,3-propane sultone are different, as shown in Table 1. The rest is the same as the preparation method of Example 1. Among them, DTD in the auxiliary additive is vinyl sulfate, and RPS is acrylic lactone.

[0090] Table 2 Parameters of Examples and Comparative Examples

[0091]

[0092]

[0093] Performance Testing

[0094] The sodium ion batteries prepared in the above examples and comparative examples were subjected to the following performance tests.

[0095] 1. First effect test:

[0096] The battery was placed at 25°C for 2 h, charged at a constant current of 0.5C to 4.0V, then charged at a constant voltage to a current of 0.03C, and the charging capacity C1 was recorded; the battery was discharged at a constant current of 1C to 1.5V, and the discharge capacity C2 was recorded.

[0097] First effect (%) = C2 / C1×100%.

[0098] 2. High temperature cycle performance test:

[0099] The formed battery was placed at 45°C for 2 hours, charged to 4.0V at a constant current of 0.5C, and then charged to 0.03C at a constant voltage; discharged to 1.5V at a constant current of 1C, and the discharge capacity C3 of the first week was recorded. After 400 cycles of charge and discharge, the discharge capacity C4 of the 400th week was recorded.

[0100] Capacity retention rate after 400 cycles of high temperature cycling (%) = C4 / C3×100%.

[0101] The gas production of the battery is tested by measuring the weight of the liquid displaced to convert the gas production of the battery. During the first week of charging and discharging, after the battery is fully charged, the weight of the liquid displaced by the battery G1 is tested and recorded. After the battery is fully charged in the 400th week, the weight of the liquid displaced by the battery G2 is tested and recorded.

[0102] The gas production of the battery after 400 cycles of high temperature (mL) = G2-G1.

[0103] 3. Normal temperature cycle performance test:

[0104] The formed battery was placed at 25°C for 2 hours, charged to 4.0V at a constant current of 0.5C, and then charged to 0.03C at a constant voltage; discharged to 1.5V at a constant current of 1C, and the discharge capacity C3 of the first week was recorded. After 400 cycles of charge and discharge, the discharge capacity C4 of the 400th week was recorded.

[0105] Capacity retention rate after 400 cycles at room temperature (%) = C4 / C3×100%.

[0106] 4. Conductivity test:

[0107] The conductivity test reference standard HG / T 4067-2015, the conductivity meter uses DDSJ-308A instrument: range 0.000μS / cm~199.9mS / cm, conductivity electrode is type 1 and type 10 electrode (platinum black). Before use, calibrate with potassium chloride standard solution at 25℃: C(KCl)=0.1mol / l (standard value 12.88mS / cm). During the test, insert the electrode and temperature sensor into the beaker containing electrolyte, put the beaker into the thermostatic bath and keep it at 25℃, and read the value after the indication is stable.

[0108] 5. DCIR test after battery capacity division

[0109] At 25°C, place the battery aside for 5 minutes, charge it at a constant current rate of 1C to the upper cut-off voltage, and then charge it at a constant voltage until the current is less than or equal to 0.05C. At this time, the battery's state of charge (SOC) is 100%. Then place it aside for 5 minutes, and then discharge it at a constant current rate of 1C to adjust the state of charge (SOC) of the sodium ion secondary battery to 50%. After placing it aside for 30 minutes, discharge it at a rate of 1C for 10 seconds. The voltage before discharge is recorded as U1, and the voltage after discharge is recorded as U2. Then the battery's DCIR = (U1-U2) / 1C.

[0110] 6. Battery internal resistance

[0111] The internal resistance of the battery is tested after the battery is fully charged for the first time. Specifically, at 25°C, charge at a constant current rate of 1C to the upper cut-off voltage, and then charge at a constant voltage until the current is less than or equal to 0.05C. At this time, the battery's state of charge (SOC) is 100%, and the internal resistance of the battery is tested.

[0112] The test results are shown in Table 2-5.

[0113] Table 2 Performance data of Examples 1-17 and Comparative Examples 1-11

[0114]

[0115]

[0116] It can be seen from Tables 1 and 2 that, compared with Comparative Examples 1-3, there is no sodium supplement additive or sodium salt additive in Comparative Example 1, the battery has low first efficiency, high internal resistance and poor cycle performance; sodium supplement additive is added in Comparative Example 2, the battery first efficiency is slightly improved, but the battery performance is still poor; there is no sodium supplement additive in Comparative Example 3, sodium salt additive is added to the electrolyte, the conductivity of the electrolyte is improved, but the battery first efficiency is low, the internal resistance is high and the cycle performance is poor; it shows that adding sodium supplement additive to the battery can play a role in sodium supplement and improve the first efficiency of the battery; adding sodium salt additive is helpful to improve the conductivity of the electrolyte. Compared with Comparative Examples 4-5, Example 7 has a mass content a of sodium supplement additive added to the battery less than 5%, the battery first efficiency is low, the mass content a of sodium supplement additive added is greater than 10%, the battery first efficiency is low, DCIR is high, the internal resistance is high, and the cycle performance is poor. It is speculated that the mass content a of sodium supplement additive added to the battery is greater than 10%, the sodium supplement additive decomposes, and the residual by-products will destroy the interface film, increase the battery internal resistance, and reduce the battery first efficiency and cycle performance. In Example 1, the mass content b of the sodium salt type sodium supplement additive in the electrolyte is less than 1%, the conductivity of the electrolyte is low, and the internal resistance of the battery increases. When b is greater than 10%, although the conductivity of the electrolyte is improved, the internal resistance of the battery is high and the cycle performance is poor. It is speculated that adding a sodium salt type sodium supplement additive b between 1% and 10% in the electrolyte can improve the conductivity of the electrolyte, and at the same time participate in the formation of the electrode interface film, protect the positive and negative electrodes, and effectively solve the problem of poor conductivity of the sodium supplement additive and the damage of the positive and negative electrodes by the residual by-products. In Example 6-7, the particle size c of the negative active material is less than 2μm or c is greater than 12μm, and the battery has low first efficiency, high DCIR, high internal resistance, low cycle capacity retention rate, and high gas production. Comparing Examples 1-17 with Comparative Examples 10-11, although the mass content a of the sodium supplement additive is between 5% and 10%, the mass content of the sodium salt additive b is between 1% and 10%, and the particle size c of the negative electrode active material is between 2 and 12 μm, the values ​​of a, b, and c do not satisfy the relationship 0.3≤a / (b+c)≤1.5, the battery has low initial efficiency, poor cycle performance, high internal resistance, and high DCIR test impedance after battery capacity division, indicating that a, b, and c in the battery must not only satisfy 5≤a≤10, 1≤b≤10, and 2≤c≤12, but also satisfy 0.3≤a / (b+c)≤1.5, so as to ensure the optimal conductivity of the positive electrode while effectively improving the conductivity of the electrolyte and the diffusion and transmission rate of ions in the negative electrode material, thereby effectively reducing the overall internal resistance of the battery and improving the initial efficiency and cycle performance of the battery.

[0117] By comparison of Examples 1-4, it can be seen that in the battery, taking the total mass of the positive electrode active material and the sodium supplement additive as 100%, the mass content of the sodium supplement additive is a, and a is in the range of 5.5% to 9%, the battery has a high first efficiency, a high capacity retention rate for normal temperature cycle and high temperature cycle, and a low internal resistance. By comparison of Examples 5-9, it can be seen that the mass content b of the added sodium salt type additive in the electrolyte is between 2% and 6%. While the electrolyte has a relatively high conductivity, the internal resistance of the battery is low and the cycle capacity retention rate is high. By comparison of Examples 10-13, it can be seen that the particle size c of the negative electrode active material in the battery is in the range of 3 to 9 μm, the battery has a high first efficiency, a low DCIR, a high cycle capacity retention rate, low gas production, and a low internal resistance. By comparison with Examples 1-17, the values ​​of a, b, and c in the battery satisfy the range of 5≤a≤10, 1≤b≤10, 2≤c≤12, and satisfy 0.5≤a / (b+c)≤1.2. The battery has higher first efficiency and cycle performance, and the battery internal resistance is also lower.

[0118] Comparing Example 1 with Example 17, the electrolyte of Example 17 does not contain 1,3-propane sultone additive, the battery cycle capacity retention rate is low, the gas production is high, and the first efficiency is low, indicating that the addition of 1,3-propane sultone (PS) to the electrolyte can effectively inhibit the occurrence of side reactions on the positive electrode surface and the dissolution and precipitation of metal ions on the positive electrode surface, stabilize the positive electrode crystal structure, effectively reduce the battery internal resistance and gas production, and improve the cycle performance.

[0119] Table 3 Battery performance data of Example 1 and Examples 18-21

[0120]

[0121] It can be seen from Tables 1 and 3 that, in comparison between Example 1 and Examples 18-21, different types of sodium supplement additives are added to the battery, and the first efficiency, internal resistance, DCIR, cycle capacity retention rate and gas production of the battery are basically similar, indicating that as long as the sodium supplement additive meets the Na x M y O z The compound shown in Formula 1, wherein 0.2<x / y<9, 0<y<6, 2≤z≤9, and M is selected from one or more of Nb, V, Ta, Mn, Fe, Cr, Co, Ni, Cu, Zn, Mg, Ti, Si, Sn, Ce, and Zr, all have the effect of improving the first efficiency and cycle performance of the battery and reducing the internal resistance of the battery.

[0122] Table 4 Battery performance data of Example 1 and Example 22-23

[0123]

[0124] It can be seen from Tables 1 and 4 that, by comparing Example 1 with Examples 22-23, different types of sodium salt type additives are added to the electrolyte, and the first efficiency, internal resistance, DCIR, cycle capacity retention rate and gas production of the battery are basically similar, indicating that different types of sodium salt type additives provided in the present application have the effect of improving the first efficiency and cycle performance of the battery and reducing the internal resistance of the battery.

[0125] Table 5 Battery performance data of Example 1 and Examples 24-31

[0126]

[0127] It can be seen from Tables 1 and 5 that, in comparison between Example 1 and Examples 24-28, the mass content of 1,3-propane sultone added to the electrolyte and the mass content of 1,3-propane sultone added to Examples 27-28 are not within the range of 0.5% to 2%, and the battery has high DCIR, high internal resistance, high gas production, and low cycle capacity retention rate, indicating that the mass content of 1,3-propane sultone (PS) added to the electrolyte is within the range of 0.5% to 2%, which can effectively inhibit the occurrence of side reactions on the positive electrode surface and the dissolution and precipitation of metal ions, stabilize the positive electrode crystal structure, effectively reduce the battery internal resistance and gas production rate, and improve the cycle performance. When the PS content added to the electrolyte is within the range of 1% to 2%, the battery has low internal resistance and gas production.

[0128] Comparing Example 1 with Examples 29-30, 1,3-propane sultone and auxiliary additives were added to the electrolyte of Examples 29-30, and the DCIR and internal resistance of the battery were reduced, the cycle gas production was greatly reduced, the first efficiency was increased, and the cycle capacity retention rate was improved. This shows that the addition of 1,3-propane sultone to the electrolyte, in conjunction with the auxiliary additives, has the effect of reducing the DCIR, internal resistance and gas production of the battery, and improving the first efficiency and cycle performance of the battery.

[0129] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A sodium ion battery, characterized in that: The invention comprises a non-aqueous electrolyte, a positive electrode and a negative electrode, wherein the non-aqueous electrolyte comprises an additive, wherein the additive comprises a sodium salt type additive, the positive electrode comprises a positive electrode active material layer, wherein the positive electrode active material layer comprises a sodium supplement additive and a positive electrode active material, wherein the sodium supplement additive is a sodium-rich transition metal oxide; the negative electrode comprises a negative electrode active material, The sodium ion battery satisfies the following relationship: 0.3≤a / (b+c)≤1.5, and 5≤a≤10, 1≤b≤10, 2≤c≤12; Wherein, the total mass of the sodium supplement additive and the positive electrode active material is 100%, a is the mass content of the sodium supplement additive, unit %; b is the mass content of the sodium salt type additive in the non-aqueous electrolyte, in %; c is the particle size of the negative electrode active material, in μm.

2. The sodium ion battery according to claim 1, characterized in that The sodium ion battery satisfies the following relationship: 0.5≤a / (b+c)≤1.

2.

3. The sodium ion battery according to claim 1, characterized in that: The total mass of the sodium supplement additive and the positive electrode active material is 100%, and the mass content a of the sodium supplement additive is in the range of 5.5-9.

4. The sodium ion battery according to claim 1, characterized in that The sodium salt additive includes one or more of sodium bis(fluorosulfonyl)imide, sodium difluorooxalatoborate, and sodium difluorophosphate; The mass content b of the sodium salt additive in the non-aqueous electrolyte is in the range of 2% to 6%.

5. The sodium ion battery according to claim 1, characterized in that: The particle size c of the negative electrode active material is in the range of 3 μm to 9 μm.

6. The sodium ion battery according to claim 1, characterized in that: The additive further comprises 1,3-propane sultone, and the mass content of the 1,3-propane sultone in the non-aqueous electrolyte is 0.5% to 2%.

7. The sodium ion battery according to claim 6, characterized in that: The mass content of the 1,3-propane sultone in the non-aqueous electrolyte is 1% to 2%.

8. The sodium ion battery according to claim 1, characterized in that: The sodium-rich transition metal oxide includes a compound shown in Formula 1, Na x M y O z Formula 1 Among them, 0.2<x / y<9, 0<y<6, 2≤z≤9, and M is selected from one or more of Nb, V, Ta, Mn, Fe, Cr, Co, Ni, Cu, Zn, Mg, Ti, Si, Sn, Ce, and Zr.

9. The sodium ion battery according to claim 8, characterized in that: The sodium-rich transition metal oxide includes one or more of Na5NbO5, Na3NbO4, Na4Nb2O7, Na5VO5, Na3VO4, and Na3TaO4.

10. The sodium ion battery according to claim 1, characterized in that: The non-aqueous electrolyte further comprises an electrolyte salt, an auxiliary additive and a non-aqueous organic solvent. The electrolyte salt includes at least one of sodium hexafluorophosphate, sodium trifluoromethylsulfonyl imide, sodium trifluoromethylsulfonate, sodium tetrafluoroborate, sodium perchlorate, sodium hexafluoroarsenate, sodium trifluoroacetate, sodium tetraphenylborate and sodium bis(trifluoromethylsulfonyl)imide; The mass content of the electrolyte salt is 8% to 14% based on the mass of the electrolyte solution being 100%; The auxiliary additive includes at least one of 1,4-butane sultone, acrylic acid lactone, vinyl sulfate and fluoroethylene carbonate; Taking the mass of the electrolyte as 100%, the mass content of the auxiliary additive is 2.5% to 10%; The non-aqueous organic solvent includes at least one of carbonates with 3 to 5 carbon atoms, carboxylates with 2 to 6 carbon atoms, and ethers with 4 to 10 carbon atoms; The positive electrode active material includes at least one of layered transition metal oxides, Prussian compounds, phosphate compounds, and sulfate compounds; The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes one or more of a carbon-based material, a silicon-based material, and a tin-based material.

Citation Information

Patent Citations

  • Sodium-rich transition metal oxide composite sodium-supplementing positive electrode active material, positive electrode material, positive electrode, preparation of positive electrode and application of positive electrode in sodium-ion battery

    CN111293290A

  • Sodium ion battery

    CN116031488A

  • Sodium ion battery

    CN116231047A

  • Sodium ion secondary battery

    CN116247282A

  • Non-aqueous electrolyte solution for sodium ion secondary battery and sodium ion secondary battery

    JP2019046614A

Cited By

  • Positive electrode slurry and sodium ion battery

    CN120376646A